The Trans-Neptunian Object (84922) 2003 VS2 through Stellar Occultations - Benedetti Rossi, Gustavo (2019)
We present results from three world-wide campaigns that resulted in the detections of two single-chord and one multi-chord stellar occultations by the plutino object (84922) 2003 VS2. From the single-chord occultations in 2013 and 2014 we obtained accurate astrometric positions for the object, while from the multi-chord occultation on 2014 November 7, we obtained the parameters of the best-fitting ellipse to the limb of the body at the time of occultation. We also obtained short-term photometry data for the body in order to derive its rotational phase during the occultation. The rotational light curve present a peak-to-peak amplitude of 0.141 ± 0.009 mag. This allows us to reconstruct the 3D shape of the body, with principal semi-axes of a = 313.8 ± 7.1 km, = - + b 265.5 9.8 8.8 km, and = - + c 247.3 43.6 26.6 km, which is not consistent with a Jacobi triaxial equilibrium figure. The derived spherical volume equivalent diameter of - + 548.3 44.6 29.5 km is about 5% larger than the radiometric diameter of 2003 VS2 derived from Herschel data of 523 ± 35 km, but still compatible with it within error bars. From those results we can also derive the geometric albedo ( - + 0.123 0.014 0.015) and, under the assumption that the object is a Maclaurin spheroid, the density r = - + 1400 300 1000 for the plutino. The disappearances and reappearances of the star during the occultations do not show any compelling evidence for a global atmosphere considering a pressure upper limit of about 1 microbar for a pure nitrogen atmosphere, nor secondary features (e.g., rings or satellite) around the main body.